PENGARUH PENGGUNAAN MEDIA AL-ASAFEER PADA PEMBELAJARAN MAHARAH KALAM SISWA - Eza, Nazdirah Uluhiyah Al Ulya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to determine the influence of Al-Asafeer media use in learning speaking skills student. The researcher used a quantitative method with data collection techniques using Observation, Interview, Test, and Documentation. The researcher used a sample of 55 students. it is known that the average learning outcome of the experimental class is 87.58 and the average learning outcome of the control class is 75.96, so it can be concluded that the average learning outcome of the experimental class is more than 11.62 compared to the control class. Furthermore, through the calculations that have been carried out using the t- test, the t table from df 53 at the significance level of 5% is 1.674.So the t value is calculated > t table (7,476 > 1.674), it can be known that the value of Sig (2-tailed) is 0.000, meaning that Sig (2-tailed) < 0.05 then H1 is accepted and H0 is rejected.